Balancing Radiation Dose Reduction and Image Quality in Chest Computed Tomography using Silicon Rubber-barium Sulfate Composite Shield - Mohammad Keshtkar; Saeedeh Yazdanifar (Journal of Medical Signals and Sensors)
Background: During chest CT examinations, the breasts are exposed to a significant amount of radiation, increasing the risk of radiation-induced cancers. The objective of this study is to develop and evaluate a novel silicon rubber-barium sulfate (BaSO4) composite breast shield for reducing radiation dose in chest computed tomography (CT) examinations while minimizing impact on image quality. Methods: Four breast shields were fabricated: one with 10% bismuth and three with 10%, 15%, and 20% BaSO4. Dose reduction was assessed using a thorax phantom and ionization chamber. Image quality effects were evaluated in the thorax phantom by measuring noise and CT number changes. The 10% barium shield was further tested on 22 patients undergoing chest CT. Results: The 10%, 15%, and 20% barium shields reduced breast dose by 36.8%, 38.6%, and 45.6%, respectively, while the 10% bismuth shield achieved a 63.1% reduction. However, the 10% barium shield had minimal impact on image quality, increasing lung noise by only 0.3 Hounsfield units (HU) and shifting CT numbers by 4.7 HU. In patient studies, 81.8% of scans showed no artifacts, with 18.2% showing slight artifacts. Conclusion: The 10% BaSO4 shield effectively reduced breast dose while maintaining image quality, presenting a viable alternative to bismuth shielding for radiation protection in chest CT examinations.